Preparation of a novel monoclonal antibody against caprine interleukin-17A and its applications in immunofluorescence and immunohistochemistry assays - Yang Gao; Feng Feng Sang; De Lan Meng; Yi Wang; Wen Tao Ma; De Kun Chen (BMC Biotechnology, 2019)
Abstract Background Interleukin-17 (IL-17), the characteristic cytokine secreted by T helper 17 lymphocytes (Th17 cells), plays a pivotal role in host defense and many inflammatory or autoimmune diseases. The aim of this study was to obtain purified protein caprine IL-17A (cIL-17A) as an antigen for preparing an IL-17A-specific monoclonal antibody (mAb). Results The coding sequence (CDS) region of cIL-17A was cloned from the peripheral blood mononuclear cells (PBMCs) of dairy goats and then inserted into the expression vector PET 32a and transformed into competent TransB (DE3) cells. Recombinant fusion protein obtained under optimized conditions was used to immunize BALB/c mice for preparing monoclonal antibodies. Finally, the supernatants of two hybridoma cell lines showing positive reaction with the recombinant fusion protein and negative reaction with fusion tags of PET 32a were collected for western blot, immunofluorescence (IF) and immunohistochemistry (IHC) analysis. Our results showed that the maximum amount of soluble protein could be obtained directly in the supernatant when the recombinant expression cells were induced by isopropyl-β-d-thiogalactoside (IPTG) at a concentration of 0.3 mmol/L at 16 °C for 42 h. Western blot analysis showed that the mAb H8 could recognize the eukaryotically expressed cIL-17A in the supernatant of transfected HEK293T cells. Immunofluorescence and immunohistochemistry assays showed that mAb H8 could strongly recognize both the eukaryotically expressed and natural cIL-17A. Conclusions The monoclonal antibody mAb H8 prepared in this study may be a potential tool for the detection of cIL-17A and beneficial for investigating the pathogenesis of various IL-17-associated diseases.